Padrões de diversidade beta de macroinvertebrados bentônicos frente ao gradiente de recuperação ambiental em riachos temperados acidificados. - Bertoncin, Ana Paula dos Santos (2022)
The industrial advance of Europe between the 19th and 20th centuries resulted in major environmental impacts. Among these impacts, the deposition of acid compounds through acid rain stands out, and this phenomenon led to the acidification of water bodies. However, from the 1980s on, with the application of stricter environmental regulations, a gradual recovery of abiotic parameters began, including pH values, which began to return to less acidic ranges. Thus, we investigated the responses of the benthic community to the gradual recovery of abiotic variables after years of intense acidification, analyzing changes in community structure and, specifically, variations in beta diversity. The study was developed with data from streams in Wales, collected and provided by two research projects that monitor the region's water bodies. The streams were classified according to abiotic characteristics and the surrounding vegetation (Acid Forest, Acid Moorland and Circumneutral Moorland). In the first approach, the community of 69 streams was analyzed, testing whether (i) the composition of macroinvertebrate communities differed among the types of environments and years analyzed; and whether (ii) in early years beta diversity among streams was lower than in more recent years, as well as in streams of a more acidic category. Samples were collected in 1984, 1995, and 2012, with the earliest year under the greatest influence of acidification. A segregation in macroinvertebrate composition was observed between 1984 and the other years, and this difference in community composition between the years suggests that environmental recovery with rising pH values, allowed the entry and establishment of new macroinvertebrate species in the streams. The lowest beta diversity value was also observed in 1984, indicating biotic homogenization in this period and an increase in community dissimilarity over time. In the second approach, we investigated the hypothesis that a gradual increase in temporal beta diversity (TBI) values occurs over time. This was done by sampling eight streams in Wales over the period 1985 to 2018, and comparing beta diversity between the reference year 1985 with all other years. There was an increase in TBI values over the years for all environments, showing evidence of biological recovery concomitant with restoration of abiotic values. The results contributed to the understanding that the biotic community also responds to environmental recovery, and there are different ways to evaluate this process, such as beta diversity. The importance of long-term research is emphasized so that such changes can be monitored.